Pressure and pressure derivative analysis for non-newtonian pseudoplastic fluids in double-porosity formations - Escobar, Freddy-Humberto; Zambrano, Angela-Patricia; Giraldo, Diana-Vanessa; Cantillo, José-Humberto (CT&F - Ciencia, Tecnología y Futuro, 2011)
Non-Newtonian fluids are often used during various drilling, workover and enhanced oil recovery processes. Most of the fracturing fluids injected into reservoir-bearing formations possess non-Newtonian nature and these fluids are often approximated by Newtonian fluid flow models. In the field of well testing, several analytical and numerical models taking into account Bingham, pseudoplastic and dilatant non-Newtonian behavior have been introduced in the literature to study their transient nature in porous media for a better reservoir characterization. Most of them deal with fracture wells and homogeneous formations and well test interpretation is conducted via the straight-line conventional analysis or type-curve matching. Only a few studies consider the pressure derivative analysis. However, there exists a need of a more practical and accurate way of characterizing such systems. So far, it does not exist any methodology to characterize heterogeneous formation bearing non-Newtonian fluids through of well test analysis. In this study, an interpretation methodology using the pressure and pressure derivative log-log plot is presented for non-Newtonian fluids in naturally fractured formations, so the dimensionless fracture storativity ratio, ω, and interporosity flow parameter, λ, are obtained from characteristics points found on such plot. The developed equations and correlations are successfully verified by their application only to synthetic well test data since no actual field data are available. A good match is found between the results provided by the proposed technique and the values used to generate the simulated data.